2016
DOI: 10.1155/2016/6343927
|View full text |Cite
|
Sign up to set email alerts
|

Demographical, Clinical, and Psychological Characteristics of Users and Nonusers of an Online Platform for T2DM Patients (e-VitaDM-3/ZODIAC-44)

Abstract: Background. Online platforms offer opportunities for support in changing lifestyle and taking responsibility for one's health, but engaging patients with type 2 diabetes is challenging. Previous studies have shown that patients interested in platforms were more often male, younger, and higher educated. This study aims to investigate differences in clinical and psychological characteristics between users and nonusers of a newly developed platform. Methods. A prospective study started in the Drenthe region of Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In this retrospective cohort study, patients were selected using the electronic health records (EHRs) of two large Dutch diabetes care networks (DCNs) that routinely collect individual patient data and have been frequently used for research . General practitioners and practice nurses from the participating practices recorded these data in the EHRs from the start of diabetes diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this retrospective cohort study, patients were selected using the electronic health records (EHRs) of two large Dutch diabetes care networks (DCNs) that routinely collect individual patient data and have been frequently used for research . General practitioners and practice nurses from the participating practices recorded these data in the EHRs from the start of diabetes diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…In this retrospective cohort study, patients were selected using the electronic health records (EHRs) of two large Dutch diabetes care networks (DCNs) that routinely collect individual patient data and have been frequently used for research. [15][16][17][18][19] General practitioners and practice nurses from the participating practices recorded these data in the EHRs from the start of diabetes diagnosis. They use the information in the EHRs for the treatment and follow-up of their patients and as proof that they provided the care as agreed upon with health insurers for declaration purposes; therefore, it can be considered accurate.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…In a previous study, the online care platform used for this study (e-Vita) showed that users of the platform had lower glycated hemoglobin (HbA1c) levels and reported higher quality of life, better well-being, lower diabetes-related distress, and better medication adherence than non-users [5]. However, the usage of this platform has been shown to be minimal in the past [5,31]. Only 11% of the patients who were interested in the use of a care platform logged on at least once [31].…”
Section: Description Of the Platformmentioning
confidence: 92%
“…However, the usage of this platform has been shown to be minimal in the past [5,31]. Only 11% of the patients who were interested in the use of a care platform logged on at least once [31]. An improved version of the online platform e-Vita was used in our study.…”
Section: Description Of the Platformmentioning
confidence: 99%
“…A fifth research project was conducted to evaluate the impact of the PHR on health care utilization (cost-effectiveness). The evaluations of all three PHRs so far showed that the actual use of the PHR is lagging [2830] and only marginal (health) improvements were found [2932]. Concrete reasons for the underperformance of the PHR remained unclear in these studies.…”
Section: Methodsmentioning
confidence: 99%